The changing role of vocational education and training in Europe: Concepts and Models - Markowitsch, Jörg [Verfasser]; Grollmann, Philipp [Verfasser] (My University, 2019)
"The article presents a synopsis of key concepts and models developed in the course of a comprehensive comparative research project carried out for Cedefop which analysed changes of vocational education and training systems between 1995 and 2015 in the EU-28, Iceland and Norway. We sketch a framework of descriptors used to analyse national conceptions of Vocational education. Building upon this framework we introduce a two-dimensional model to describe trajectories of national VET systems. The German-speaking and Nordic countries are used as examples to illustrate the model. The aim of the contribution is to discuss the potential of these new methods and models for comparative VET research." (authors' abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2 Europa; T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildungssystem; Europa; Internationaler Vergleich; Vergleichende Berufsbildungsforschung; Modellierung; Typologie